2015
DOI: 10.1111/cup.12578
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous basal cell carcinosarcoma: case report and literature review

Abstract: Carcinosarcomas are malignant neoplasms with biphasic carcinomatous and sarcomatous or sarcoma-like components. In general, the sarcomatous component is accepted to be the result of divergent mesenchymal differentiation of the epithelial component. Although well characterized in some anatomic locations (e.g. uterus, upper aerodigestive tract and lung), carcinosarcomas of the skin are rare. Reported epithelial components include squamous, adnexal, neuroendocrine and basaloid. Including this case, only 47 cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 37 publications
2
30
1
Order By: Relevance
“…3d). These histological and immunohistological characteristics were consistent with those of the previously reported case of basal cell CS [2]. Both epithelial and mesenchymal components were 70–80% positive for Ki-67, which suggested that the mesenchymal cells represented a sarcomatous progression of BCC, resulting in a diagnosis of basal cell CS.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…3d). These histological and immunohistological characteristics were consistent with those of the previously reported case of basal cell CS [2]. Both epithelial and mesenchymal components were 70–80% positive for Ki-67, which suggested that the mesenchymal cells represented a sarcomatous progression of BCC, resulting in a diagnosis of basal cell CS.…”
Section: Resultssupporting
confidence: 89%
“…The sarcomatous components has been recognized as a metaplastic carcinoma of the epithelial components [2]. Metaplastic carcinoma demonstrates the proliferation of spindle cells sometimes associated with ossification and chondrification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter has been included in the well‐known and broad group of metaplastic carcinoma, but currently, it is regarded as a particular subset with different risk factors than the common hormone‐related adenocarcinomas of the breast . Primary cutaneous biphasic sarcomatoid carcinomas are very rare, with approximately 50 cases reported in the literature . In most of those cases, the epithelial component is a BCC or SCC, with only five published cases associated with porocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…5 Primary cutaneous biphasic sarcomatoid carcinomas are very rare, with approximately 50 cases reported in the literature. 6 In most of those cases, the epithelial component is a BCC or SCC, with only five published cases associated with porocarcinoma. When malignant heterologous differentiation is present in the tumor, it is usually in the form of osteosarcoma, chondrosarcoma, rhabdomyosarcoma, or leiomyosarcoma.…”
Section: Pathologic Findingsmentioning
confidence: 99%